A High‐Density Azobenzene Side Chain Polymer Brush for Azimuthal and Zenithal Orientational Photoswitching of a Nematic Liquid Crystal. Issue 6 (13th February 2019) - Mukai, Koji; Imai, Kenjiro; Hara, Mitsuo; Nagano, Shusaku; Seki, Takahiro
Abstract: The azimuthal and zenithal orientational switching of nematic liquid crystals (NLCs) can be performed by photoresponsive azobenzene alignment layers called command surfaces. Such photoresponsive layers have been prepared by molecular assembly methods or by spincasting of polymer materials. This work reports on the photoswitching orientation behavior of an NLC on a high‐density brush of an azobenzene‐containing side chain liquid crystalline polymer. On the high‐density polymer brush surface, the zenithal homeotropic/planar photoalignment switching modes triggered by UV/visible light irradiation are reversed from those observed for traditional command surface systems, reflecting the azobenzene side chain orientation directing parallel to the substrate surface. Because the thermally stable trans ‐azobenzene provides the in‐plane orientation of the NLC, irradiation with linearly polarized visible light readily switches the azimuthal direction to an arbitrary direction, and the resulting orientation is retained persistently. This paper discusses the features of the architecture of a high‐density polymer brush as the command surface for NLC orientation. Abstract : This way please ! The orientation photoswitching behavior of a nematic liquid crystal on a high‐density brush of an azobenzene‐containing side chain liquid crystalline polymer is studied. The brush polymer surface provided the reversed modes of photoalignment from those observed for traditional command surface systems, reflecting the azobenzene side chain orientation directing parallel to the substrate surface.